2022
DOI: 10.3389/fphar.2022.1049818
|View full text |Cite
|
Sign up to set email alerts
|

Naringin attenuates fructose-induced NAFLD progression in rats through reducing endogenous triglyceride synthesis and activating the Nrf2/HO-1 pathway

Abstract: Background: Excessive fructose consumption causes hepatic lipid accumulation via increased triglyceride (TG) synthesis, leading to the development and progression of non-alcoholic fatty liver disease (NALFD). Naringin, a flavanone glycoside found in citrus fruit, has antioxidant and hypolipidemic properties. Therefore, the aim of this study was to investigate the effect of naringin on fructose-induced NAFLD in rats and the possible underlying mechanism.Methods: Male Sprague Dawley rats were given 10% (w/v) fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…This study demonstrated that naringin from orange peel extract might ameliorate T2DM-induced testicular dysfunction via its antioxidant and anti-inflammatory activities, and XO/UA could be a target for the gonado-protective strategy of naringin. These findings agree with the study of Pengnet et al [ 42 ], Adebiyi et al [ 43 ], and Pengnet et al [ 44 ], which reported that naringin (a major constituent of orange peel) suppressed oxido-inflammatory response by maintaining redox balance. In addition to a redox balance restoration, naringin restored the testicular histoarhitecture and function by preventing seminiferous tubular distortion, spermatogenic cell degeneration, and loss of Leydig cells within the interstitial spaces.…”
Section: Discussionsupporting
confidence: 93%
“…This study demonstrated that naringin from orange peel extract might ameliorate T2DM-induced testicular dysfunction via its antioxidant and anti-inflammatory activities, and XO/UA could be a target for the gonado-protective strategy of naringin. These findings agree with the study of Pengnet et al [ 42 ], Adebiyi et al [ 43 ], and Pengnet et al [ 44 ], which reported that naringin (a major constituent of orange peel) suppressed oxido-inflammatory response by maintaining redox balance. In addition to a redox balance restoration, naringin restored the testicular histoarhitecture and function by preventing seminiferous tubular distortion, spermatogenic cell degeneration, and loss of Leydig cells within the interstitial spaces.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, hepatoprotective and anti-inflammatory effects of naringin in NAFLD lie in inhibiting NF-κB and MAPK signaling. In line with this, naringin has been shown to reverse the upregulation of NF-κB and TNF-α expression in rat liver in fructose-induced rat NAFLD animal models and target activation of antioxidant mediator Nrf2/HO-1 pathways to block fructose-induced NAFLD progression in rats [ 147 ]. As NAFLD progresses, it may become a common chronic liver disease, and liver fibrosis develops.…”
Section: Resultsmentioning
confidence: 96%
“…We recently demonstrated in long-term SRD-fed rats that liver injury and oxidative stress are accompanied by decreased NrF2 expression and increased NF-κB p65 protein expression in the liver [12]. In this line, Pengnet et al [63] showed that NF-κB expression was increased and NrF2 expression was decreased in the liver of fructose-fed rats during 12 weeks. Hernandez-Rodas et al [64] demonstrated significantly decreased hepatic NrF2 DNA binding and increased hepatic NF-κB DNA binding in male C57BL/6J mice fed with a high-fat diet for 12 weeks.…”
Section: Discussionmentioning
confidence: 99%